Income Transfers and Support for Mothers' Employment: The Link to Family Poverty Risks. A Comparison between Italy, Sweden and the UK - Cristina Solera (Luxembourg Income Study (LIS), 1998)
For a growing number of children in families headed by single mothers and in those headed by two adults with limited job skills, economic security now depends on mothers' earnings. The role that income transfers plays in reducing child poverty is well understood. Much less investigated is the effect of policies that support mothers' employment on the economic well-being of families with children. Yet, both dimensions of social policies seem crucial in the explanation of cross-national variations in child poverty rates. In this study we explore these questions by comparing three countries (Italy, UK and Sweden) with different social policy approaches. Since the LIS data for Italy do not provide information on taxes and other public transfers, in order to obtain a meaningful evaluation of the effectiveness of the income transfer system, we have integrated them with a recent microsimulation model of Italian personal income taxes, social security contributions and family allowances.
Keywords: 330; Weibliche Arbeitskräfte; Mutterschutz; Familienleistungsausgleich; Armutsbekämpfung; Vergleich; Großbritannien; Italien; Schweden